Pharmacovigilance signal detection of psychiatric adverse events induced by third-generation antiepileptic drugs in children - Sun, Wenfang; Li, Yali; Xia, Binbin; Li, Liushui; Chen, Jing; Liu, Yang; Pang, Jingyao; Liu, Fang; Cheng, Hua (Frontiers in Pharmacology, 2026)
ObjectiveThe present study was a retrospective pharmacovigilance analysis to identify pharmacovigilance signals of psychiatric adverse events (AEs) associated with the clinical use of third-generation antiepileptic drugs (AEDs) in children, thereby providing a reference for clinical drug selection and pharmaceutical care.MethodsThe data were obtained from the United States Food and Drug Administration (FDA) Adverse Event Reporting System (FAERS). Reports involving patients under 18 years old were retrieved using the generic and brand names of four drugs: lacosamide, perampanel, brivaracetam, and eslicarbazepine. Positive safety signals were detected using the Reporting Odds Ratio (ROR) method and the Bayesian Confidence Propagation Neural Network (BCPNN) method for further analysis. The number of AEs ≥3 cases, ROR value 95% confidence interval lower limit >1 and information component 25 (IC025) must be above 0 was considered statistically significant.ResultsLacosamide and eslicarbazepine acetate demonstrated relatively lower signals of psychiatric AEs, while brivaracetam was associated with a certain degree of psychiatric risk. In contrast, perampanel requires heightened clinical vigilance due to its potential to induce severe psychiatric and behavioral abnormalities, particularly aggression, suicidal ideation, and homicidal ideation. The most significant psychiatric safety signals for perampanel, based on ROR, were homicidal ideation (ROR = 23.51 [9.72, 56.89]), aggression (ROR = 17.81 [13.85, 22.92]), and psychotic disorders (ROR = 16.94 [9.57, 29.99]).ConclusionThe findings of this study provide a reference for clinical selection of third-generation AEDs. When initiating treatment in children, clinicians should consider the differential psychiatric risk profiles of these third-generation AEDs, monitor potential psychiatric side effects and adjust prescriptions promptly.